Photocatalytic remediation of harmful Alexandrium minutum bloom using hybrid chitosan-modified TiO2 films in seawater: a lab-based study - Ibrahim, Nur Hanisah; Iqbal, Anwar; Mohammad Noor, Normawaty; Mohd Razali, Roziawati; Sreekantan, Srimala; Yuli Yanto, Dede Heri; Mahadi, Abdul Hanif; Wilson, Lee D. (MDPI, 2022)
The uncontrolled growth of harmful algal blooms (HABs) can negatively impact the environment and pose threats to human health and aquatic ecosystems. Titanium dioxide (TiO2) is known to be effective in killing harmful algae through flocculation and sedimentation. However, TiO2 in a dispersed form can harm other non-target marine organisms, which has raised concerns by environmentalists and scientists. This research seeks to explore the utility of immobilized titanium oxide as a photocatalyst for mitigation of HABs, where the Alexandrium minutum bloom was used as a model system herein. Chitosan was modified with 0.2 wt.% TiO2 (Chi/TiO2 (x mL; x = 1, 3 and 5 mL) and the corresponding films were prepared via solvent casting method. Scanning electron microscope (SEM) images of the films reveal a highly uneven surface. X-ray diffraction (XRD) analysis indicates the reduction in chitosan crystallinity, where the presence of TiO2 was negligible, in accordance with its dispersion within the chitosan matrix. The photocatalytic mitigation of A.minutum was carried out via a physical approach in a laboratory-scale setting. The negative surface charge of the films was observed to repel the negatively charged A.minutum causing fluctuation in the removal efficiency (RE). The highest RE (76.1 ± 13.8%) was obtained when Chi/TiO2 (1 mL) was used at 72 h, where the hydroxyl radicals generated were inferred to contribute to the deactivation of the algae cells by causing oxidative stress. An outcome of this study indicates that such hybrid films have the potential to replace the non-immobilized (dispersed) TiO2 for HAB mitigation. However, further investigation is required to deploy these films for field applications at a larger scale.